2014
DOI: 10.1155/2014/301304
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Antiacne Plant Drugs: Contribution to Modern Therapeutics

Abstract: Acne is a common but serious skin disease, which affects approximately 80% adolescents and young adults in 11–30 age group. 42.5% of men and 50.9% of women continue to suffer from this disease into their twenties. Bacterial resistance is now at the alarming stage due to the irrational use of antibiotics. Hence, search for new lead molecule/bioactive and rational delivery of the existing drug (for better therapeutic effect) to the site of action is the need of the hour. Plants and plant-derived products have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 141 publications
3
57
0
1
Order By: Relevance
“…HNK has been applied to treat neurodegenerative diseases, such as Alzheimer's disease [22] , and has potential anti-diabetic [23] , anti-acnegenic [24] , anti-viral [25] , anti-tumoral [26] and other activities. Our previous study showed that HNK effectively inhibits the proliferation of NSCLC cells through the induction of apoptosis and inhibition of autophagy and also at least partially promotes the apoptosis of NSCLC cells induced by TRAIL by reducing c-FLIP expression levels [15,18] .…”
Section: Discussionmentioning
confidence: 99%
“…HNK has been applied to treat neurodegenerative diseases, such as Alzheimer's disease [22] , and has potential anti-diabetic [23] , anti-acnegenic [24] , anti-viral [25] , anti-tumoral [26] and other activities. Our previous study showed that HNK effectively inhibits the proliferation of NSCLC cells through the induction of apoptosis and inhibition of autophagy and also at least partially promotes the apoptosis of NSCLC cells induced by TRAIL by reducing c-FLIP expression levels [15,18] .…”
Section: Discussionmentioning
confidence: 99%
“…The air dried plant material was coarse powdered and subjected to methanol group 50.9% of women and 42.5% of men are susceptible to this acne vulgaris 2,3 19,20 .…”
Section: Preparation Of Extractmentioning
confidence: 99%
“…Norimam efektui pasiekti pasirenkami skirtingi vaistinių augalų naudojimo būdai -arbatos, ekstraktai, tepalai, kremai bei losjonai [5,8].…”
Section: Aptarimasunclassified